2021
DOI: 10.1136/bmjinnov-2020-000593
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning model to predict the need for mechanical ventilation using chest X-ray images in hospitalised patients with COVID-19

Abstract: ObjectivesThere exists a wide gap in the availability of mechanical ventilator devices and their acute need in the context of the COVID-19 pandemic. An initial triaging method that accurately identifies the need for mechanical ventilation in hospitalised patients with COVID-19 is needed. We aimed to investigate if a potentially deteriorating clinical course in hospitalised patients with COVID-19 can be detected using all X-ray images taken during hospitalisation.MethodsWe exploited the well-established DenseNe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…Nevertheless, they found that CXR attributes can only be used for the prediction if other features such as SpO 2 , PaO 2 , and some other clinical features are available. Likewise, Kulkarni et al [20] used the CXR for early detection of COVID-19 patients requiring venti-lator support using the DL model, and found that CXR features can be used to perform the prediction 3 days in advance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, they found that CXR attributes can only be used for the prediction if other features such as SpO 2 , PaO 2 , and some other clinical features are available. Likewise, Kulkarni et al [20] used the CXR for early detection of COVID-19 patients requiring venti-lator support using the DL model, and found that CXR features can be used to perform the prediction 3 days in advance.…”
Section: Discussionmentioning
confidence: 99%
“…The objective was to identify the significance of the features and found that along with CXR, patients' medical history and other vitals have significantly enhanced the prediction. Conversely, another study [20] utilized CXR for predicting MV support using the DenseNet121 model. The significance of the study is that the patients that require MV were identified 3 days before the event.…”
Section: Ai-based Studies For Early Identification Of Covid-19 Patien...mentioning
confidence: 99%
See 1 more Smart Citation
“…A weakly supervised learning architecture for predicting a multi-regional score on chest X-ray images was designed to effectively and reliably assess the severity of lung compromise in patients with COVID-19 [ 37 ]. In terms of clinical management, it has been reported that the DenseNet121 model can accurately predict the need for mechanical ventilation early in the hospitalization of patients with COVID-19 using chest X-ray images [ 38 ]. A DL-based model for classifying the severity of and monitoring COVID-19 was proposed.…”
Section: Medical Imaging Analysismentioning
confidence: 99%
“…For instance, differential diagnosis (Healthy, pneumonia or COVID-19) of COVID-19 positive patients can be achieved 20 – 22 with accuracies reaching over 90% using deep networks such as the Xception architecture. Disease severity can be assessed in an objective way using radiology 23 25 which is useful to quickly assess the pulmonary involvement of the disease; and the potential for adverse events can be predicted (such as death, intubation or need for oxygenation) to help direct future treatments 26 Finally, ventilation need can be predicted in the near future for hospital-admitted patients 27 with over 90% accuracy. These cases demonstrate that CXRs possess enough information to predict clinical developments in the near future (around three days ahead of the event).…”
Section: Introductionmentioning
confidence: 99%